2021
DOI: 10.15446/revfacmed.v70n1.86775
|View full text |Cite
|
Sign up to set email alerts
|

Changes in liver function test levels in HIV patients undergoing highly active antiretroviral therapy (HAART). Longitudinal study in Lima, Peru

Abstract: Introducción. Para prevenir el desarrollo de enfermedad hepática crónica en pacientes con VIH durante la Terapia Antirretroviral de Gran Actividad (TARGA) se deben estimar y monitorear cambios en el perfil hepático. Objetivo. Determinar la variación de las concentraciones del perfil hepático en pacientes con VIH durante la TARGA. Materiales y métodos. Estudio retrospectivo longitudinal realizado en 100 pacientes con VIH atendidos en el Hospital Nacional Hipólito Unanue, Lima, Perú, entre 2015 y 2017. Se incluy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Aspartate Aminotransferase levels showed a considerable difference between individuals with HIV seropositive on TLD and HIV seronegative subjects, with the former group showing lower levels. This decrease in AST levels among individuals receiving TLD suggests a potential protective effect of this anti-retroviral therapy on hepatic integrity [8]. However, further investigations are necessary to elucidate the mechanisms underlying this observation and its clinical implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspartate Aminotransferase levels showed a considerable difference between individuals with HIV seropositive on TLD and HIV seronegative subjects, with the former group showing lower levels. This decrease in AST levels among individuals receiving TLD suggests a potential protective effect of this anti-retroviral therapy on hepatic integrity [8]. However, further investigations are necessary to elucidate the mechanisms underlying this observation and its clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no significant difference was observed in ALT levels between HIV seropositive individuals on TLD and HIV seronegative subjects. Alanine Aminotransferase is a crucial enzyme indicating liver injury, and the comparable levels between the two groups suggest that TLD treatment may not significantly affect ALT activity in HIV-positive individuals [9]. Nevertheless, continuous monitoring of ALT levels is essential to detect potential hepatotoxic effects associated with TLD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…11 A longitudinal study conducted in Peru showed different results, where using ARV for three months resulted in a decline in both AST and ALT levels. 12 Intrinsic and extrinsic factors may also influence these variations in hepatotoxicity profiles in the studies' subjects. This study indicated that a sexual orientation-related variable was associated with abnormal LFT events.…”
Section: Discussionmentioning
confidence: 99%